1996
DOI: 10.1182/blood.v87.7.3012.bloodjournal8773012
|View full text |Cite
|
Sign up to set email alerts
|

Donor immunization with Haemophilus influenzae type b (HIB)-conjugate vaccine in allogeneic bone marrow transplantation

Abstract: Bone marrow transplant patients are at increased risk for infections with polysaccharide encapsulated organisms and respond poorly to polysaccharide vaccines. We evaluated the effect of donor immunization with Haemophilus influenzae type b (HIB) polysaccharide-conjugate vaccine on recipient antibody responses following allogeneic bone marrow transplantation. Thirty-two allogeneic transplant patients and their donors were immunized before transplantation with HIB-conjugate, tetanus toxoid and 23-valent pneumoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(18 citation statements)
references
References 26 publications
1
16
0
1
Order By: Relevance
“…This supports other studies suggesting that donor immunization primes recipients for early antibody responses to protein-polysaccharide conjugates (285), and may explain why others failed to demonstrate an effect of donor vaccination when recipients were vaccinated 1 year after transplantation (176). It has been suggested that donor immunization with T-independent purified polysaccharide antigens does not prime the recipient to respond to polysaccharide vaccination (176,189).…”
Section: H Influenzae Type B Vaccinessupporting
confidence: 83%
See 3 more Smart Citations
“…This supports other studies suggesting that donor immunization primes recipients for early antibody responses to protein-polysaccharide conjugates (285), and may explain why others failed to demonstrate an effect of donor vaccination when recipients were vaccinated 1 year after transplantation (176). It has been suggested that donor immunization with T-independent purified polysaccharide antigens does not prime the recipient to respond to polysaccharide vaccination (176,189).…”
Section: H Influenzae Type B Vaccinessupporting
confidence: 83%
“…The most significant correlate of decreased antibody responses in BMT recipients appears to be T-cell depletion. Neither intravenous immunoglobulin therapy nor graft-versus-host disease has been consistently shown to have an effect on Hib conjugate-induced antibody responses (116,189). Vaccination with a Hib conjugate vaccine has been suggested at 12 and 24 months after either autologous or allogeneic transplantation (8).…”
Section: H Influenzae Type B Vaccinesmentioning
confidence: 99%
See 2 more Smart Citations
“…In a similar study, allogeneic BMT recipients were allocated to one of two groups where the donor was or was not immunized before bone marrow harvest. Patients whose donors were immunized with Hib-conjugate vaccine and TT had higher antibody levels after transplantation and immunization than did patients with unimmunized donors (24). The authors suggested that recipient and/or donor immunization before bone marrow harvest and transplantation may be a strategy to prevent these and other infections in BMT patients (23,24).…”
Section: Post-bmt Vaccinationmentioning
confidence: 99%